The Effect of the Traditional Game of Gobak Sodor on Dribbling Agility in Basketball Games for Extracurricular Students - Suhadi, M; Handayani, Widya; Imansyah, Farizal (Journal of Social Work and Science Education, 2023)
Gobak sodor game is performed with the aim of increasing the agility of the players in the basketball game. This type of research is quantitative research that uses the “pre-experimental design” research method, namely (one-group pretest-posttest design). The population in this study was 40 people. The sample in this study is a total of 40 people. Based on the results of the research, it can be seen that this traditional game, in addition to being fun and motivating students in training, has other advantages, namely, it enables students to exercise. Therefore, students’ agility becomes more enhanced in driving and defending than before physical training with this game. The results of the hypothesis test show that the calculated t value is greater than the table t (9.102 > 2.021). Thus, the alternative hypothesis (Ha) is accepted which reads there is a significant effect of traditional gobak sodor game on dribbling agility in basketball games for extracurricular students at SD Negeri 72 OKU.